2019
DOI: 10.1002/jhet.3631
|View full text |Cite
|
Sign up to set email alerts
|

New Biphenyl‐Based Bispyrazolines: Synthesis, Antimicrobial, and Docking Studies

Abstract: In this study, a series of new bispyrazolines 8(a–f) have been prepared from the cyclization reactions of bischalcones 7(a–f) with phenyl hydrazine by refluxing under the alkaline alcoholic (KOH/EtOH) conditions. The O‐alkylation reactions of hydroxyl substituted chalcone 6 with different 1,ω‐dibromoalkanes in the presence of anhydrous potassium carbonate, tetrabutylammonium iodide, and dry acetone afforded the symmetrical new bischalcones 7(a–f) in good yields. Chalcone 6 was realized by using the Claisen–Sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…These bis heterocycles were obtained with yields between 70 to 80%. In vitro antifungal evaluation against F. oxysporum showed that these compounds have moderate activity, bis pyrazoline 62 , which exhibited the best activity (MIC between 16 µg/mL) and their corresponding intermediates bis chalcones [ 94 ].…”
Section: Synthetic Methods For Highly Active Compounds Against Fox Speciesmentioning
confidence: 99%
“…These bis heterocycles were obtained with yields between 70 to 80%. In vitro antifungal evaluation against F. oxysporum showed that these compounds have moderate activity, bis pyrazoline 62 , which exhibited the best activity (MIC between 16 µg/mL) and their corresponding intermediates bis chalcones [ 94 ].…”
Section: Synthetic Methods For Highly Active Compounds Against Fox Speciesmentioning
confidence: 99%
“…Owing to the significance of various heterocycles and in continuation of our research program in the synthesis of bioactive bisheterocyclic products, we reported here the synthesis of four series of novel bispyrazolines such as N ‐acetyl 3a‐d , N ‐carbothioamide 4a‐d , N ‐carboxamide 5a‐d , and N ‐phenyl 6a‐d using o/m/p ‐xylene and biphenyl aromatic chain linker. The interest behind the synthesis of these symmetrical novel bispyrazolines was to investigate the effect of N ‐substitution on pyrazoline ring upon their antimicrobial profile.…”
Section: Introductionmentioning
confidence: 99%
“…It would be highly advantageous here to develop the synthesis of rigid chain-linked new bischalcones by using the ordinary protocols and to investigate their chemical transformations in search of new symmetrical bisheterocycles. [38][39][40][41] Owing to the significance of various heterocycles and in continuation of our research program in the synthesis of bioactive bisheterocyclic products, [42][43][44][45][46] we reported here the synthesis of four series of novel bispyrazolines such as N-acetyl 3a-d, N-carbothioamide 4a-d, N-carboxamide 5a-d, and N-phenyl 6a-d using o/m/p-xylene and biphenyl aromatic chain linker. The interest behind the synthesis of these symmetrical novel bispyrazolines was to investigate the effect of Nsubstitution on pyrazoline ring upon their antimicrobial profile.…”
Section: Introductionmentioning
confidence: 99%